Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Sosialisasi Perpajakan Sebagai Variabel Moderating: Studi Kasus Wajib Pajak Kendaraan Bermotor Kantor Samsat Surabaya Timur - Intan Maharani Febrilianingrum; Munari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze how much influence the variables of E-Samsat understanding, taxpayer awareness, tax sanctions have on motor vehicle taxpayer compliance with tax socialization as a moderating variable at the East Surabaya Samsat Office. This research uses a survey method by giving questionnaires to registered taxpayers who come when the survey is carried out at the East Surabaya Samsat Office. Determination of the sample using the accidental sampling method. The number of samples in this study was 100 respondents. The results of this research indicate that understanding E-Samsat and tax sanctions contributes positively to motor vehicle taxpayer compliance, taxpayer awareness does not contribute positively to motor vehicle taxpayer compliance, tax socialization weakens understanding of E-Samsat, taxpayer awareness, and tax sanctions against motor vehicle tax compliance.